Evaluation of the Correlation between Chondromalacia Patellae and the Thickness of Subcutaneous Knee fat using Magnetic Resonance Imaging - Navami Shetty; Vijaya Holla Kayyar (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: Chondromalacia Patellae is a condition that involves softening and degeneration of the articular hyaline cartilage of the Patellae that articulates with the trochlear groove of the femur. To evaluate the correlation between subcutaneous fat thickness around the knee joint with the presence or absence of chondromalacia Patellae/severity of chondromalacia Patellae in MRI.Material and methods:  A retrospective review were conducted of knee MRIs in 100 patients referred to the department of radiodiagnosis for MRI imaging of the knee. The assessment was done for the presence or absence of chondromalacia Patellae and graded positive studies from 0 (absent) to 3(full cartilage thickness defect). Measurement of subcutaneous knee fat thickness was obtained on the medial, lateral, and prepatellar aspects of the knee.Results: The subcutaneous thickness values were significantly different between patients with or without chondromalacia Patellae.  Mean values of normal and patients with chondromalacia Patellae vary with severity. The proportionate increase in the subcutaneous fat thickness values is observed with higher grades of chondromalacia Patellae.  Mean subcutaneous fat thickness values were seen to be on the higher side in female patients compared to male patients.Conclusions: This is the first study to evaluate the correlation between subcutaneous knee fat thickness in three aspects (medial, anterior, and lateral) of knee circumference and chondromalacia Patellae. The study shows a positive relationship between the subcutaneous knee fat thickness and chondromalacia Patellae. This indirectly indicates the role of obesity in the development of chondromalacia Patellae. This positive relationship can be crucial in spreading awareness and preventive care.